2022
DOI: 10.3389/fmicb.2022.866462
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes – How This Pathogen Survives in Food-Production Environments?

Abstract: The foodborne pathogen Listeria monocytogenes is the causative agent of human listeriosis, a severe disease, especially dangerous for the elderly, pregnant women, and newborns. Although this infection is comparatively rare, it is often associated with a significant mortality rate of 20–30% worldwide. Therefore, this microorganism has an important impact on food safety. L. monocytogenes can adapt, survive and even grow over a wide range of food production environmental stress conditions such as temperatures, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 287 publications
(431 reference statements)
0
59
1
Order By: Relevance
“…Serotypes 1/2a, 1/2b, and 4b account for the majority of human listeriosis cases and food contamination ( 3 , 7 , 8 ). Biofilm production in L. monocytogenes is related to persistent food contamination and thereby human infection ( 24 , 25 ). However, studies have presented conflicting results regarding the association between biofilm formation and phylogeny and serotype ( 5 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Serotypes 1/2a, 1/2b, and 4b account for the majority of human listeriosis cases and food contamination ( 3 , 7 , 8 ). Biofilm production in L. monocytogenes is related to persistent food contamination and thereby human infection ( 24 , 25 ). However, studies have presented conflicting results regarding the association between biofilm formation and phylogeny and serotype ( 5 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes is a frequently isolated and sometimes a persistent contaminant within food industry settings (35)(36)(37). As such, extensive efforts are made to control this pathogen throughout the food supply chain, especially in food production environments, where Listeria is commonly transferred to food products by cross contamination from surfaces in production facilities (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…ListShield is a cocktail composed of six bacteriophages with high lytic activity against Listeria strains. It was shown that it significantly reduces the presence of pathogens in various types of RTE foods, with the efficiency of 82–99% [ 64 ]. Ishaq et al (2022) reported that in the case of smoked salmon, the use of ListShield completely inhibited the growth of L. monocytogenes on naturally contaminated samples as well as those infected in an in vitro experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…The product showed high specificity in trials performed at different temperatures. The largest decrease in bacterial count achieved was 4.44 log CFU/mL when the inoculum count was 3 log CFU/g [ 64 ]. Importantly, Listex P100 has also been proved to be effective in reducing the biofilm structure formed by L. monocytogenes on stainless steel with a reduction of 3.5–5.4 log CFU/cm 2 compared to a control group in which no antibacterial agent was applied [ 67 ].…”
Section: Introductionmentioning
confidence: 99%